2001
DOI: 10.1007/bf03343866
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine effects of subcutaneous sumatriptan in patients with migraine

Abstract: We evaluated the sensitivity of 5-HT1D receptors in patients with migraine using sumatriptan as a pharmacological probe. The drug inhibits the release of ACTH, cortisol and prolactin and this effect may be used to explore the function of serotoninergic systems in vivo. We administered sumatriptan (6 mg sc) and placebo to 15 migraineurs, during the headache-free period, and to 10 healthy controls. Blood samples were collected -15, 0, 15, 30, 45, 60 and 90 min after injections. Sumatriptan induced a significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
2
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 25 publications
0
11
2
1
Order By: Relevance
“…27 In a previous study concerning episodic migraine, by the use of a specific neuroendocrine tool, we found a normal function of the HPA axis. 28 On the contrary, the present study in chronic migraine patients shows a significant impairment of the HPA axis. Both ACTH and cortisol responses to hCRH resulted significantly increased in CM-MOH patients.…”
Section: Commentscontrasting
confidence: 85%
See 1 more Smart Citation
“…27 In a previous study concerning episodic migraine, by the use of a specific neuroendocrine tool, we found a normal function of the HPA axis. 28 On the contrary, the present study in chronic migraine patients shows a significant impairment of the HPA axis. Both ACTH and cortisol responses to hCRH resulted significantly increased in CM-MOH patients.…”
Section: Commentscontrasting
confidence: 85%
“…In a variety of chronic pain conditions and in patients with mood disorders a dysfunction of the HPA axis was shown, due to an impairment at different levels of negative feedback mechanisms 27 . In a previous study concerning episodic migraine, by the use of a specific neuroendocrine tool, we found a normal function of the HPA axis 28 . On the contrary, the present study in chronic migraine patients shows a significant impairment of the HPA axis.…”
Section: Commentscontrasting
confidence: 61%
“…Stattdessen werden, insbesondere beim Clusterkopfschmerz, chronobiologische Auffälligkeiten in der zirkadianen Rhythmik verantwortlich gemacht, wobei offenbar übergeordnete Störungen hypothalamischer Zentren zugrunde liegen. Diese Annahme wird durch andere schmerzunabhängige Sekretionsstörun-gen anderer Hormone wie Melantonin, Prolaktin, GH und TSH [25] [26]. Das ebenfalls häufig in der Schmerztherapie eingesetzte Carbamazepin führt bei längerer Anwendung zu einem primär hypophysär ausgelösten Hyperkortisolismus bei gleichzeitiger Verminderung von CRH [24].…”
Section: Chronische Schmerzenunclassified
“…Plasma concentrations of ACTH and cortisol were assessed before the tourniquet and at 5 and 10 min during the tourniquet test (Fig. 1C), according to standard clinical practice and as described previously (Rainero et al, 2001;Benedetti et al, 2003). Briefly, blood samples were collected just before and at 5 and 10 min of the tourniquet in sterile tubes and immediately centrifuged at 4°C, and the plasma was stored at Ϫ80°C until assayed.…”
mentioning
confidence: 99%